Political Ethics by Sheikh Hasina And Khaleda Zia’s Government from 2009 to Present: A Research on Literature Review - Mohammad Eisa Ruhullah; Zuly Qodir (Khazanah Sosial, 2020)
The principal motive of this research is to analyze the status of ethical, democratic government and Public Services in Bangladesh. This paper examines the state of democratic governance in various rulers of Bangladesh, especially during Sheikh Hasina and Khaleda Zia’s governmental from 2009 to present. With qualitavie method This paper begins with a conceptual analysis of democratic governance and then identifies several vital problems. This article explains the status of ethical, democratic public services in Bangladesh in terms of some critical elements/elements of democratic governance, including the development of democratic institutions. Furthermore, processes, strengthening electoral and law enforcement systems, improving access to justice through freedom to the division of power, and encouraging citizen participation. Answer promoting tolerance, transparency, promoting democratic values and respect of liberty in public services with good governance and ethics, which are very infrequent in current Bangladesh politics.